Factors influencing the length of stay in the emergency department - Jajang Rahmat Solihin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Hospitals provide public access to medical care and healthcare services related to health recovery. The Ministry of Health has set a length of stay (LOS) quality standard for Cileungsi Regional Hospital at 6 hours, aiming to deliver fast and timely services to patients from their arrival at the Emergency Department (ED) until their admission to the inpatient ward. Purpose: To determine the factors associated with the length of stay in the Emergency Department. Method: A quantitative descriptive design with a cross-sectional method through observations conducted at Cileungsi Regional Hospital in June 2024. Sampling was carried out using random selection based on Slovin's formula, following pre-determined inclusion and exclusion criteria, resulting in 70 respondents. The independent variables in this study include severity level, nurse response time, and bed availability, while the dependent variable is the length of stay of patients. Results: The majority of respondents were aged 46-55 years (39 respondents, 55.7%). Female respondents accounted for 52 individuals (74.3%). Most respondents had completed high school (48 respondents, 68.6%). The majority of patients had a long length of stay (52 respondents, 74.3%). Statistical tests showed that the p-values for the variables triage, response time, inpatient bed availability, patient arrival time during shifts (morning, afternoon, evening), patient arrival volume, and ancillary examination duration were all < 0.05, indicating a significant relationship with length of stay in the ED. Conclusion: There is a significant relationship between triage, response time, inpatient bed availability, patient arrival time during shifts (morning, afternoon, evening), patient arrival volume, and ancillary examination duration with the length of stay in the ED (p < 0.05).